Good Families of Barcelona : A Social History of Power in the Industrial Era - McDonogh, Gary W. (Book collections on Project MUSE., 1986)
Gary McDonogh combines ethnology and history to analyze the organization, reproduction, and decline of an urban industrial elite. Using Barcelona as the foundation for more general consideration of power-holding groups, he tells the story of the Good Families," those few hundred lineages who have dominated the city in the nineteenth and twentieth centuries. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.